Minocycline protects against neuronal mitochondrial dysfunction and cognition impairment - Motaghinejad, Majid; Motevalian, Manijeh; Ulloa, Luis; Kaviani, Neda; Hamurtekin, Emre (Nencki Inst Experimental Biology, 2023)
The potential of minocycline to protect against methylphenidate-induced neurodegeneration has been extensively reported in the literature but the mechanism of action is still unknown. This study aims to determine the role of mitochondrial chain enzymes and redox homeostasis on the neuroprotective effects of minocycline in methylphenidate-induced neurodegeneration. Wistar adult male rats were randomly assigned to the seven experimental groups: Group 1 received saline solution; Group 2 received methylphenidate (10 mg/kg, i.p.); Groups 3, 4, 5, and 6 received methylphenidate and minocycline for 21 days; Group 7 received minocycline alone. Cognition was evaluated with the Morris water maze test. Activity of the hippocampal mitochondrial quadruple complexes I, II, III and IV, mitochondrial membrane potential, adenosine triphosphate (ATP) levels, total antioxidant capacity, and reactive oxygen species were determined. Treatment with minocycline inhibited methylphenidate-induced cognitive dysfunction. Minocycline treatment increased mitochondrial quadruple complex activities, mitochondrial membrane potential, total antioxidant capacity, and ATP levels in the dentate gyrus and cornu ammonis-1 (CA1) areas of the hippocampus. Minocycline is likely to confer neuroprotection against methylphenidate-induced neurodegeneration and cognition impairment by regulating mitochondrial activity and oxidative stress.
Keywords: methylphenidate; minocycline; mitochondria; cognition